Pendampingan Revitalisasi Sasi sebagai Upaya Penguatan Ketahanan Sosial-Ekologis di Negeri Lima Maluku Tengah - Muhtar Muhtar; Yustina Sopacua; Amir Faisal Kotarumalos; Saiful Rizal Mahulauw; Rukoyah Rukoyah (Indo Publishing, 2026)
This community service activity entitled “Assistance for the Revitalization of Sasi as an Effort to Strengthen Social-Ecological Resilience in Negeri Lima” was conducted in Negeri Lima, Leihitu District, Central Maluku Regency. The activity was motivated by the declining implementation of sasi values, weakening community participation in coastal environmental management, and increasing social-ecological pressures caused by environmental degradation and climate change in coastal areas. The purpose of this program was to strengthen the social-ecological resilience of coastal communities through the revitalization of sasi as a local wisdom-based coastal resource management system. The implementation method used a participatory and collaborative approach involving village government, customary leaders, youth groups, women groups, and coastal communities. The stages of activities included problem identification, socialization, Focus Group Discussion (FGD), institutional strengthening assistance, and program evaluation. The results of the activity showed an increase in community understanding regarding the role of sasi as an instrument for natural resource management, social control mechanism, preservation of local cultural values, and strengthening social solidarity. Community participation in discussions and environmental awareness activities also increased significantly. In addition, stronger coordination was established between the village government and customary institutions in supporting community-based coastal management. The program also produced recommendations for strengthening customary regulations, participatory environmental monitoring, youth involvement, and local culture-based environmental education. Overall, the revitalization of sasi contributed positively to strengthening the social-ecological resilience of the coastal community in Negeri Lima and became an initial model for sustainable local wisdom-based coastal governance.